Adsorption performance of layered double hydroxides for heavy metals removal in soil with the presence of microplastics. Issue 6 (December 2022) - Huang, Hanhan; Li, Zhaosong; Wang, Haiyan; Xia, Caifeng; Yan, Pingke; Zhang, Qian; Meng, Zilin
Abstract: Microplastics (MPs) are widely presence in soil, and the uncertain influence of MPs is ineluctable. In this study, the influence of removal efficiency for heavy metals by LDHs with the presence of polyethylene (PE) and polypropylene (PP) is investigated. And the removal efficiency of heavy metals Cu 2+, Pb 2+, Zn 2+, Ni 2+ by LDHs from soil is investigated by contact time, initial concentration, PP/PE contents, pH and coexisting ions. The adsorption capacities of heavy metals with the presence of PP/PE are larger and the effects with high content of PP/PE is more obvious on removal of heavy metals. The isothermal experiment data are well described by the Generalized Langmuir isothermal model, denoting that the adsorption sites on the absorbents are certain, and the sites are inhomogeneous with different adsorption energy. In order to further explore the influence of PP/PE on the removal of heavy metals by LDHs, the interaction between LDHs and PP/PE is analyzed by XRD, FT-IR, Zeta potential and SEM. The sites energy distribution theory is employed to analyze the distribution of accessible adsorption sites and the heterogeneity of sites. The results show that with the presence of PP/PE in soil, LDHs interacts with PP/PE preferentially on account of electrostatic attraction, and the combination of LDHs and PP/PE increases the accessible adsorption sites for the removal of heavy metals and is beneficial to the adsorption process. These findings contribute to understanding environmental behavior of heavy metals with the presence of MPs and guide the application of LDHs in soil. Graphical Abstract: ga1 Highlights: The presence of PP/PE influenced the heavy metals removal by LDHs from soil. LDHs and PP/PE combined preferentially through electrostatic attraction. Active sites with heterogeneous energy determined removal process by GL model. Increased sites by combination of PP/PE proved by site energy distribution theory.